Analysis of Students' Mathematics Learning Outcomes on Matrix Concepts: A Comparative Study - Palinussa, Anderson Leonardo; Limehuwey, Jean; Ayal, Carolina Selfiana (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
21st-century education requires students to be skilled and excel in science, technology, and mathematics, but many countries complain about declining student achievement. Therefore, teachers can apply the right learning strategy to improve student learning outcomes. This study aimed to determine the differences in student learning outcomes taught using the TTW (Think Talk Write) type cooperative learning model and the NHT (Numbered Head Together) learning model on matrix material. The type of this research is experimental research. This research uses a research design, namely The posttest group design. The population in this study were all students of class XI Public Senior High School 19 West Seram, a total of 40 students. The sample in this study used saturated sampling, namely class XI MIA1 with a total of 20 students and class MIA2 with a total of 20 students, so the total sample in this study was 40 students. The instrument used in this study is a test instrument consisting of description questions. The results showed that students' math learning outcomes with the TTW model were superior to those taught with the NHT model. Therefore, the TTW model can be recommended for improving students' mathematics learning outcomes on matrix topics.